NOx reduction in waste incinerators by selective catalytic reduction (SCR) instead of selective non catalytic reduction (SNCR) compared from a life cycle perspective: a case study. (20th January 2016) - Van Caneghem, Jo; De Greef, Johan; Block, Chantal; Vandecasteele, Carlo
Abstract: In most modern waste incinerators selective non catalytic reduction (SNCR) is applied to remove NOx from the combustion gas to reach the European emission limit value (ELV) of 200 mg/Nm 3 . If however the NOx -ELV for waste incinerators would be lowered to e.g. 100 mg/Nm 3, SNCR, with a typical NOx removal efficiency of around 50%, would not suffice to reach the new ELV. In that case, selective catalytic reduction (SCR), with a NOx removal efficiency of up to 90% in tail-end configuration could be an interesting alternative. However, from a life cycle perspective, the production, construction and operation of SCR equipment including the catalyst, also involve indirect (i.e. not from the process itself but related to other parts of the life-cycle) pollutant emissions and resource consumption with resulting environmental impacts. By means of a case study of a typical hazardous waste incinerator it is illustrated that replacing SNCR by tail-end SCR reduces the direct environmental impact of the incinerator (i.e. environmental impact of the NOx emitted at the stack) in the impact categories acidification, eutrophication and photo-oxidant formation, as expected from the lower NOx emissions in case of SCR. However, mainly due to the need to reheat the combustion gas, SCR has higher indirect impacts than SNCR, most notably in the impact category global warming. Because of these indirect impacts, the mentioned direct environmental impact reductions of SCR in the impact categories acidification, eutrophication and photo-oxidant formation are no net environmental benefits; when e.g. fuel oil is used as an energy source to reheat the flue gas, the indirect impact in the impact categories acidification and photo-oxidant formation is higher than the direct impact reduction related to the lower NOx concentration in the flue gas emitted at the stack of the installation. In this case, there is only a net environmental benefit in the impact category eutrophication. Overall it can be concluded that in the hazardous waste incinerator under study, which is representative in its field, replacing SNCR by SCR to reach a new, lower ELV, increases the net overall environmental impact of the incinerator, particularly in the impact category global warming. From an environmental point of view optimizing SNCR should be preferred over installing tail-end SCR in existing installations such as the considered hazardous waste incinerator. Highlights: SCR has a has a higher NOx removal efficiency than SNCR. Switching from SNCR to SCR reduces the direct environmental impact of a typical hazardous waste incinerator. The indirect environmental impacts of SCR are higher than those of SNCR. Switching from SNCR to SCR increases the net environmental impact of the incinerator in the impact category global warming. From an environmental point of view optimizing existing SNCR should be preferred.